1990
DOI: 10.1007/bf02030236
|View full text |Cite
|
Sign up to set email alerts
|

The role of erythropoietin in the anaemia of chronic disease in rheumatoid arthritis

Abstract: We reviewed studies on the role of erythropoietin (Epo) in the anaemia of chronic disease (ACD) in rheumatoid arthritis (RA). A relatively impaired Epo response to the anaemia was found in a number of studies although in others serum Epo level was the same as in other types of anaemia. Some arguments are found in favor of a reduced bone marrow-Epo sensitivity although these reflect results mainly from in vitro experiments. It is not yet established whether bone marrow macrophage Epo production is impaired in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…It is demonstrated that high-dose r-Hu-Epo effectively improves Hb levels in ACD in RA. These findings confirm that an impaired Epo responsiveness to the anemia is one of the major factors in the pathogenesis of ACD in RA, as has been postulated by various authors [1,4,5,23,26]. Apparently, this phenomenon can be overcome by the administration of exogenous Epo.…”
Section: Discussionsupporting
confidence: 73%
“…It is demonstrated that high-dose r-Hu-Epo effectively improves Hb levels in ACD in RA. These findings confirm that an impaired Epo responsiveness to the anemia is one of the major factors in the pathogenesis of ACD in RA, as has been postulated by various authors [1,4,5,23,26]. Apparently, this phenomenon can be overcome by the administration of exogenous Epo.…”
Section: Discussionsupporting
confidence: 73%
“…However, serum ferritin level is limited as a marker to determine iron storage in RA patients, as ferritin is one of the acutephase proteins [15]. Serum EPO levels in RA patients with anaemia are lower than those in IDA patients, unrelated to haemoglobin concentration [16][17][18]. We also found that serum EPO levels in 24 RA patients with anaemia were relatively low, i.e.…”
Section: Discussionmentioning
confidence: 80%
“…Serum TfR levels are high in patients with IDA or autoimmune hemolytic anaemia (AIHA), and low in aplastic anaemia [6][7][8]. In addition, it has been shown that sTfR levels differ between IDA and ACD [16][17][18][19]-i.e. s-TfR levels in ACD are higher than normal but lower than those in IDA [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of studies focused on the role of an impaired erythropoietin (Epo) responsiveness to the anaemia in ACD. It is not unlikely that, in ACD in RA, Epo responsiveness to the anaemia and, perhaps, bone marrow epo sensitivity are decreased (2). Boyd and Lappin recently published a very interesting study concerning the role of Epo responsiveness in ACD in this journal (3).…”
Section: Interactions Between Erythropoietin and Iron Metabolism In Amentioning
confidence: 99%